Evaluation of groundwater quality using linear regression model - Mohammad Muqtada Ali Khan; Rashid Umar; Md. Azizul Baten; Habibah Lateh (2012)
The present study was undertaken to analyzed chemical parameters of groundwater samples were collected from representative sampling stations established over entire study area in post monsoon 2005, and pre monsoon 2006 periods from 37 locations in parts of the Central Ganga Plain. Eight parameters such as, TDS, HCO3, Cl, SO4, Na, K, Ca, and Mg were selected as the groundwater quality variables in this study. Total dissolved solids (TDS) were calculated by summing up the concentrations of all the major cations and anions. The concentrations of Ca++, Mg++, Cl-, HCO3 - and total hardness were determined by volumetric method. Ca++ and Mg++ were determined by EDTA titration. For HCO3 -, HCl titration to a methyl orange point was used. Chloride was determined by titration with AgNO3 solution. Flame emission photometry was used for the determination of Na+ and K+. Sulphate was determined by gravimetric method. The higher values of TDS, Na, K, and Cl were recorded in pre monsoon 2006 compared to post monsoon 2005. On the other hand the higher values of Ca, Mg, HCO3, and SO4 were observed in post monsoon 2005 than pre monsoon 2006. This showed clear impact of land use on groundwater. The regression analysis between TDS-Na; TDS-K; TDS –HCO3; showed strong positive relationship as r = 0.802, 0.715, and 0.786 respectively, and moderate positive correlation with Cl ions (r= 0.579) and very low positive correlation (r= 0.055, 0.324 and 0.330) with Ca, Mg, and SO4. All the estimated chemical parameter values were found to be statistically significant in both pre and post monsoon years.